2018
DOI: 10.1590/abd1806-4841.20186366
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy in tinea manuum

Abstract: Tinea manuum is a dermatophytosis which is often mistaken for other keratodermas, especially palmar psoriasis and chronic hand eczema. We report the use of dermoscopy as a diagnostic aid in a case of tinea manuum. The dermoscopic clue turned out to be the presence of whitish scaling located mainly in the furrows. This aspect has never been seen in other keratodermas and therefore can be considered as a useful finding to assist in the recognition of tinea manuum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…We find whitish scales mainly located in the furrows [1,27]. they could result from the predilection of dermatophytes to proliferate in a humid environment, such as the palmar furrows [27]. The fundus is often erythematous (Fig.…”
Section: Tinea Manummentioning
confidence: 86%
See 1 more Smart Citation
“…We find whitish scales mainly located in the furrows [1,27]. they could result from the predilection of dermatophytes to proliferate in a humid environment, such as the palmar furrows [27]. The fundus is often erythematous (Fig.…”
Section: Tinea Manummentioning
confidence: 86%
“…5g). Although unilateral or asymmetric involvement and concurrent infection of other sites (particularly the nails and feet) may be useful in aiding the diagnosis of TM, its distinction from similar inflammatory dermatoses is often difficult, resulting in diagnostic delays, errors and unnecessary therapies [26,27].…”
Section: Tinea Manummentioning
confidence: 99%
“…Tinea manuum. Lately, dermoscopy of tinea manuum has been reported, showing predominant scaling associated with dotted vessels detectable in the furrows [17,18]. Pthirus pubis.…”
Section: Tinea Corporis Numerous Papers Have Been Publishedmentioning
confidence: 99%
“…Jakhar et al also reported that dotted vessels only in the skin furrows is another dermatoscopic finding in tinea manuum. They explained this vascular finding with the reactionary vasodilatation of vessels in response to inflammatory process induced by dermatophytes [5,51,52].…”
Section: Dermatoscopymentioning
confidence: 99%